ANALISIS PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS IT UNTUK PENINGKATAN HASIL BELAJAR - Kristia Setyaningsih; Sumarno; Ida Dwijayanti (STKIP Subang, 2024)
The purpose of this study is to determine the analysis of student needs on IT-based learning media. The research method used is qualitative descriptive. The selected research projects were 13 respondents and 44 teachers in Semarang district. The instrument used is in the form of a questionnaire for media use needs. The results of this study show that grade III students of SDN Pasekan 01 need IT-based learning media. With the hope that students will more easily understand the material and be more interested in learning so that student learning outcomes can increase.